The Technological Enhancement of Normally Occurring Radioactive Materials in Red Mud due to the Production of Alumina. (16th March 2016) - Miller, Maurice O.; Miller, Dionne A.
Abstract : This study investigates the level of technological enhancement of normally occurring radioactive materials (TENORM) in the red mud waste due to the production of alumina in Jamaica. Technological enhancements factors (TEF) were determined for the uranium, thorium, actinium series, their progenies, and the nonseries potassium-40 using gamma spectrometry. The study concluded that bauxite production technologically enhances the uranium progenies Th-234, Pb-214, Bi-214, and Pa-234 and the thorium-232 progenies Ac-228, Pb-212, and Bi-212 in red mud. The actinium series was technologically enhanced, but K-40 and the thorium daughter, Tl-208, were reduced. The spectrometric comparison of Tl-208 (at 510 keV) was unexpected since its other photopeaks at 583 keV, 934 keV, and 968 keV were markedly different. An explanation for this anomaly is discussed. An explanation regarding the process of accumulation and fractionation of organically derived phosphate deposits and potassium-feldspar is offered to explain the spectrometric differences between the alumina product and its waste material, red mud.